Early indirect selection for nitrogen use efficiency in maize - Caixeta, Débora; Fritsche-Neto, Roberto; Granato, Ítalo Stefanine; Oliveira, Lucimar; Galvão, João Carlos (Revista Ciência Agronômica, 2015)
Several studies to evaluate nitrogen use efficiency (NUE) have been carried out using early growth stages. However, there are no scientific reports on the ideal stage for evaluation and on which characteristics have the highest correlation with the NUE at that stage. The aim therefore was to identify the phenological stages and secondary characteristics which maximize accuracy in early indirect selection for NUE in maize. To do this, three endogamic maize strains were evaluated in a completely randomised design with five replications, in a triple factorial scheme (strains x N levels x phenological stage), at two contrasting nitrogen levels: low and high nitrogen. The plants were evaluated at five growth stages: stage nine (V9), with 14 fully-developed leaves (V14), tasseling (VT), flowering (R1) and physiological maturity (R6). The following characteristics were evaluated: efficiency in the usage, absorption, use and translocation of nitrogen; activity of nitrate reductase and glutamine synthetase; length of the lateral and axial roots; specific root area; chlorophyll content; number of leaves; plant height; stem diameter; and the levels of phosphorus and potassium. Considering the estimated direct and indirect gains, it can be concluded that the activities of glutamine synthetase at the V9 and V14 stages permit early indirect selection for nitrogen use efficiency in maize under conditions of low and high N availability respectively.